B-line detection using amplitude modulation-frequency modulation (AM-FM) features - Chau Loo Kung, G.; Mamani, G.; Pozo Fortunić, E.; Serpa, S.; Zenteno, O.; Ramos, D.; Penã, G.; Fredes, G.; Chura, E.; Ticona, E.; Manella, H.; Lobo, V.; et al. (SPIE, 2018)
Pneumonia is one of the most common acute respiratory infections among pediatric populations worldwide. Ultrasound is becoming increasingly important in the diagnosis of lung diseases as a more portable and safer alternative to X-ray imaging. In the current work, we present a new automatic system for detection of B-lines, one of the distinctive features of pneumonic ultrasound scans, using amplitude modulation-frequency modulation (AM-FM). Features are evaluated on 109 videos obtained from 100 pediatric patients using a Verasonics V1 scanner. Further, the results were compared to the ones obtained with a previously published spectral feature (SF) method. Sensitivities of 92% and 83% and specificities of 91% and 70% were obtained on zone-1 and zone-2 of the lungs, respectively. In contrast, the SF method provided sensitivities of 72% and 68% in zone-1 and zone-2, respectively, and specificities of 68% and 46% in zone-1 and zone-2, respectively. In addition, the AM-FM method allowed increasing the F1-score when compared to the SF method from 70% to 87% and from 61% to 78% in zone-1 and zone-2, respectively. The results suggest the proposed method may be useful for the computer assisted diagnosis of pneumonia.
Keywords: Frequency modulation; Modulation (music); Ultrasound; Amplitude modulation; Amplitude; Lung; Pneumonia; Computer science; Acoustics; Biomedical engineering; Medicine; Physics; Radio frequency; Optics; Internal medicine; Telecommunications; https://purl.org/pe-repo/ocde/ford#2.06.00